(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To assess the knowledge and correct attitude towards standard precautions among healthcare workers (HCWs) at Thu Duc City Hospital and related factors in 2024. Subjects and Methods: A cross-sectional descriptive study was conducted on 618 HCWs at Thu Duc City Hospital. Results: The proportion of knowledge was 62%.Particularly, the highest figure of knowledge was related to safe injection practices and prevention of sharps injuries 92,4%, the lowest is basic knowledge of standard prevention 22.2%. In addition, the proportion of attitude was 77%. In particular, the attitude that all healthcare workers necessarily participated in annual training on standard precautions was 95.9%, besides the attitude was related to the statement “It is not necessary to clean instruments before disinfection and sterilization," at 21.2%. Conclusion: The knowledge and attitude of HCWs towards standard precautions were at a moderate level. There was a significant correlation between knowledge and attitude (p<0.05). It is necessary to continue training and enhancing knowledge and correct attitudes on standard prevention for medical staff at the hospital.